2018
DOI: 10.1080/1612197x.2018.1511621
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and influence of psychosocial factors on technical refinement amongst highly-skilled tennis players

Abstract: The present study investigated the prevalence and influence of psychosocial factors amongst a sample of highly-skilled athletes who had previously attempted to refine their technique. Semi-structured qualitative interviews were conducted with eight tennis players to gain an indepth understanding of their experiences during the process. Results revealed that participants sought to refine their technique in order to address an 'attenuated' movement pattern perceived as causing a competitive disadvantage. Address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…While this study showed that players were only partially consistent in applying the cues offered by the coach, there was a clear intention to follow the coaches' instructions. This finding aligns with Diekfuss and Raisbeck (2017), who found that "esteemed individuals", such as coaches, were influential in shaping Division 1 golfers' attentional strategies; a finding also mirrored in high-level tennis (Toner et al, 2020). This suggests, therefore, that technical training needs to be considered as an interactive biopsychosocial process, in that the player's focus (i.e., the psycho) is influenced by the physical skill being performed (i.e., the bio -long-game vs. short-game technique) and who is telling them to focus in a specific way (i.e., the social); not just simply a matter of what a player ultimately focuses on that is prioritized by theory from laboratory studies alone.…”
Section: Foci In Trainingsupporting
confidence: 86%
“…While this study showed that players were only partially consistent in applying the cues offered by the coach, there was a clear intention to follow the coaches' instructions. This finding aligns with Diekfuss and Raisbeck (2017), who found that "esteemed individuals", such as coaches, were influential in shaping Division 1 golfers' attentional strategies; a finding also mirrored in high-level tennis (Toner et al, 2020). This suggests, therefore, that technical training needs to be considered as an interactive biopsychosocial process, in that the player's focus (i.e., the psycho) is influenced by the physical skill being performed (i.e., the bio -long-game vs. short-game technique) and who is telling them to focus in a specific way (i.e., the social); not just simply a matter of what a player ultimately focuses on that is prioritized by theory from laboratory studies alone.…”
Section: Foci In Trainingsupporting
confidence: 86%
“…What is interesting is that, where previous work has recognised a distinct cost associated with the skill refinement process (Carson, Collins, 2016b), especially when not conducted in a careful and considered manner (cf. Toner, Carson, Collins, Nicholls, 2018), as an incomplete strategy TFA did not reveal any similar patterns of performance on first attempt. As such, for the sample tested here and from a distance of 8 ft., at least, we recommend that golfers might try TFA as a 'cost-free' experiment.…”
Section: Practical Implications For the Momentmentioning
confidence: 69%
“…In addition, Nicholls et al (2016) athletes' behavior may also be affected by stress the results of his study that elite athletes seriously influence the moral and ethical development of children and youth of many societies.…”
Section: Review Of Related Literaturementioning
confidence: 99%